The affordable care act and family planning services: the effect of optional medicaid expansion on safety net programs - Lanese, Bethany G. (Contracept Reprod Med, 2016)
BACKGROUND: Title X of the Public Health Service Act provides funding for a range of reproductive health services, with a priority given to low-income persons. Now that many of these services are provided to larger numbers of people with low-income since the passage of the Affordable Care Act and Medicaid expansion, questions remain on the continued need for the Title X program. The current project highlights the importance of these safety net programs. METHODS: To help inform this policy issue, research was conducted to examine the revenue and service changes for Title X per state and compare those findings to the states’ Medicaid expansion and demographics. The dataset include publicly available data from 2013 and 2014 Family Planning Annual Reports (FPAR). Paired samples differences of means t-tests were then used to compare the means of family planning participation rates for 2013 and 2014 across the different categories for Medicaid expansion states and non-expansion states. RESULTS: The ACA has had an impact on Title X services, but the link is not as direct as previously thought. The findings indicate that all states’ Title X funded clinics lost revenue; however, expansion states fared better than non-expansion states. DISCUSSION: While the general statements from the FPAR National surveys certainly are supported in that Title X providers have decreased in number and scope of services, which has led to the decrease in total clients, these variations are not evenly applied across the states. The ACA has very likely had an impact on Title X services, but the link is not as obvious as previously thought. CONCLUSION: Title X funded clinics have helped increase access to health insurance at a greater rate in expansion states than non-expansion states. There was much concern from advocates that with the projected increased revenue from Medicaid and private insurance, that Title X programs could be deemed unnecessary. However, this revenue increase has yet to actually pan out. Title X still helps fill a much needed service gap for a vulnerable population.